SISTEM INFORMASI KEUANGAN MAHASISWA AMIK IBRAHIMY SITUBONDO - Nurul Huda (Jurnal Ilmiah Informatika, 2018)
The speed and efficiency of management and dissemination of information is needed for AMIK Ibrahimy, especially the management and dissemination of student financial information. The use of manual methods that leads to less effective and less efficient work which certainly raises risks such as file damage or loss of data and of course such things are not desired by anyone. So that these problems can be slightly resolved, it is necessary to develop an information system to help ease the workload of financial staff in handling the recording, processing, and dissemination of student financial information. To make the work more effective and streamlined, a Student Financial Information System was developed at the WEB-based AMIK Ibrahimy Situbondo Class and SMS Gateway. This information system is made using HTML, PHP, CSS, Javascript, MySQL, and uses a sending and receiving message application, Gammu, which will receive requests and send information to students. In addition to printed information in the form of paper, students can obtain information about their dependents from short messages sent from the information system, and it is hoped that this information system can be beneficial for academics and students.